Insights into the structure, function, and pathophysiology of Shigella dysenteriae through pangenome analysis - Mir, Asif; Hashmi, Danial Ahmed; Qureshi, Muhammad Mustajeeb UL Haq; Faisal, Muhammad Saleem; Iqbal, Wajid (Acta Biologica Szegediensis, 2025)
Shigella dysenteriae, the causative agent of shigellosis, poses a significant global health threat due to its role in causing millions of cases of bacillary diarrhea and escalating antibiotic resistance. This study utilized bioinformatics analysis with the Pan Explorer to delve into the pangenome of S. dysenteriae. The aim was to uncover key bacterial functions, elucidate its pathogenicity and virulence, and identify factors contributing to genetic variability among strains. Results revealed a larger dispensable genome compared to the core genome and strain-specific genes. Metabolism-related Cluster of Orthologous Groups were predominant, followed by cellular processing and signaling pathways, while poorly characterized Cluster of Orthologous Groups had modest representation and those associated with information and storage processing were least prevalent. Notably, genes linked to the pathogenicity and virulence of S. dysenteriae were found in both dispensable and core genome regions, indicating their significance. Overall conservation was observed among strain genomes, but the open pangenome nature suggests potential for genetic exchange with other sources. These findings provide valuable insights for future microbial genomics research on S. dysenteriae.